On the microstructure and erosion–corrosion resistance of AlCrFeCoNiCu high-entropy alloy via annealing treatment. Issue 12 (12th August 2016) - Zhao, J. H.; Ji, X. L.; Shan, Y. P.; Fu, Y.; Yao, Z.
Abstract : As-cast AlCrFeCoNiCu high-entropy alloy (HEA) was a solid solution of body-centered cubic (BCC) and face-centered cubic phases with a typical dendrite and interdendrite structures. The precipitated intermediate phases in 600°C annealed HEA are responsible for the improved hardness. After 1000°C annealing treatment, the crystalline was re-arranged because of the decomposition of BCC phases. The 1000°C annealed HEA has the best corrosion resistance due to its re-arranged crystalline structure. Meanwhile, the 600°C annealed HEA has the best erosion–corrosion resistance for its highest hardness and its wear rate is more than two times lower than that of AISI 304 stainless steel. Therefore, the HEA has a potential application in saline–sand slurry because of its superior corrosion and erosion–corrosion resistance.